Pronouns and Thoughts on Neutrality: Gender Concerns in Modern Grammar - Brandon Darr; Tyler Kibbey (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
With increased social awareness of transgender and non-binary individuals, universities across the United States have implemented policies, made suggestions for inclusive language practices, and provided gender-neutral pronoun guides to avoid marginalizing these groups of people through adjusting personal pronoun usage. However, these measures have been met with mixed reception from students, parents, administrators, legislators, and others. As linguists, the authors looked at the situation with gender-neutral pronouns on campuses and investigated 1) an overview of how exactly language plays a role in identifying someone’s gender; and 2) the historical linguistics and social contexts that surround this issue. The paper concludes with recommendations for gender-neutral pronouns in compliance with federal policies and university visions, missions, and goals to be more inclusive of genderqueer and non-binary individuals.